TRANSKULTURASI NILAI-NILAI KEPEMIMPINAN TRANSFORMATIF DALAM PENGELOLAAN PENDIDIKAN ISLAM: Transculturation Of Transformative Leadership Values In The Management Of Islamic Education - Ahmad Fauzi (LP2M UIN KH.Achmad Siddiq Jember, 2020)
Islamic education starting from the foundational and operational, can not be adequately solved. This condition draws attention among practitioners and managers of Islamic education to be neatly disentangled and can be found at the tip of the base. Therefore, this paper briefly aims to parse the problem through a transformative leadership approach based on social values. The significance of transformative leadership as a conceptual and transformational framework in the management of education through the roles and actions of a leader. Internalization of transformative leadership is expected to be a positive energy to influence individual social action in education. The transformative leadership is based on religious and prophetic values, just as the prophetic mission becomes the dominant force in managing Islamic education and legitimizing cultural power. Such power is the social role of the individual by inspiring, enlightening, empowering, inspiring without indoctrinating, awakening without harm, arousing without compelling, and inviting without reign, through morality in achieving the aims of the organization. Thus the portrait of transformative leadership must have the ability to influence individual actions and behavior through trait approach, behavior approach, power-influence approach, situational approach, and integrative approach.